Association of complicated appendicitis on the risk of later in vitro fertilization treatment requirement and ectopic pregnancy: a nationwide cohort study. (4th June 2021) - Männistö, Jaana; Sammalkorpi, Henna; Niinimäki, Maarit; Mentula, Maarit; Mentula, Panu
Abstract: Introduction: A population‐based register study utilizing three Finnish National Registers was carried out to determine whether uncomplicated appendicitis, complicated appendicitis and appendectomy without appendicitis are associated with a subsequent risk of requiring in vitro fertilization (IVF) treatment or a risk of ectopic pregnancy among reproductive‐age women. Material and methods: A total of 23 997 women who underwent appendectomy for uncomplicated or complicated appendicitis or for nonspecific abdominal pain or who had nonspecific abdominal pain without surgical procedures between 2000 and 2012 were included in the study. The later risks of IVF treatment requirement and ectopic pregnancy were assessed after uncomplicated appendicitis, complicated appendicitis and appendectomy without appendicitis. Women with nonspecific abdominal pain without surgical procedures served as the reference group. Results: The rates of later IVF treatment after uncomplicated appendicitis, complicated appendicitis and appendectomy without appendicitis were low (2.1%, 2.5% and 2.3%, respectively; p  = 0.681). Neither appendicitis nor appendectomy was associated with the risk of requiring IVF treatment. The rate of ectopic pregnancy after uncomplicated and complicated appendicitis was very low (0.8%). Women with uncomplicated appendicitis had a significantly lower risk of ectopic pregnancy compared with patients with nonspecific abdominal pain. Conclusions: Appendicitis, whether complicated or uncomplicated, and appendectomy without appendicitis does not increase the risk of requiring later IVF treatment or the risk of ectopic pregnancy.